Writing Oneself, Writing the Other: J.M. Coetzee’s Fictional Autobiography in Boyhood, Youth and Summertime - Kusek, Robert (Department of Dutch and South African Studies, Faculty of English, 2012)
How is a writer’s life to be embodied in writing? How to tell one’s own life story? How to challenge a reader and not to imprison oneself in the modes and forms of conventional life writing? The above-posed questions remain central to J.M. Coetzee’s oeuvre who in one of the interviews with David Attwell confessed that “in a larger sense all writing is autobiography: everything that you write, including criticism and fiction, writes you as you write it” (Attwell 1999: 17). Coetzee’s difficult and highly confusing group of late twenty and early twenty-first-century works – Boyhood: Scenes from Provincial Life, Youth, Elizabeth Costello, Slow Man, Diary of a Bad Year and Summertime: Scenes from Provincial Life – focus on a variety of strategies in which a life can be represented in a literary work. These genre-bending contributions to life-writing discourse constantly challenge the readers to tell fact from invention, autobiography from fiction, never satisfying them with the answers given. Yet, they explore the intriguing figure, that is the author – in all his peculiarity, accidentalness and actuality – in a way that can hardly be matched by many other contemporary works. Mikhail Bakhtin once observed that “the process of assimilating real historical time and space in literature has a complicated and erratic history, as does the articulation of actual historical persons in such a time and space” (Bakhtin 1981: 84). The present paper focuses on three such articulations, Coetzee’s autobiographical volumes entitled Boyhood: Scenes from Provincial Life, Youth and Summertime: Scenes from Provincial Life and investigates their self-referentiality, i.e. a relationship between the ‘real’/historical ‘I’ and the narrated ‘I.’
Keywords: J.M. Coetzee; life-writing; autobiography; self-referentiality